The “Anjir” utterances in everyday communication of Gen-Z students - Zul Fauzi, Arief; Hasan, Imam; Kamal, Bahri; Setiawan, Fiki (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2025)
This study aims to analyze the meaning and function of the word "anjir" in the communication of Gen Z students at Harapan Bersama Polytechnic. The word "anjir" is a form of slang that has shifted in meaning from a curse to a symbol of emotional expression, social, and group identity. This research uses a descriptive qualitative approach with data collection techniques through observation, digital conversation documentation, and semi- structured interviews. The results of the analysis show that the word "anjir" is used in various forms such as "anjay", "bjir", "jir", and so on, each of which reflects a certain emotional intensity. In meaning, "anjir" is used to express annoyance, admiration, empathy, and cuteness. Functionally, this word acts as a spontaneous expression, a filler for casual conversation, and a strengthener of social relations among students. The findings show that the word "anjir" has become part of Gen Z's distinctive communication style that is more open, egalitarian, and contextual. This research is expected to contribute to sociolinguistic studies and an understanding of the language dynamics of the younger generation.